Rwanda : Food Smart Country Diagnostic - World Bank (World Bank, Washington, DC, 2020)
The term “food smart” refers to a food system that is efficient, meets the food needs of a country, and is environmentally sustainable. Reducing food loss and waste (FLW) is one of the critical pillars of building a smart food system. This diagnostic focuses on the FLW pillar, from farm to fork to landfill, with the objective of alerting policymakers to the role that addressing food loss and waste can play in meeting their various global and national policy commitments. Across Sub-Saharan Africa, FLW contributes to food insecurity, reduced income to farmers and communities, and greenhouse gas emissions. In Rwanda specifically, a growing population — set to nearly double to 22 million in the next 30 years — will exacerbate the food security challenge. Even today, undernourishment affects 35.6% of Rwanda’s population, and 36.9% of children are stunted.